Catalytic Activity Enhancement Of Nano Calcium Oxide Catalyst Via Thermal Hydration-Dehydration Treatment For Biodiesel Production - Chooi, Chee Yoong (2021)
The reaction rate of biodiesel production at moderate temperature can be accelerated by developing green heterogeneous nanocatalyst from waste source with desired catalytic properties besides offering environmental friendly downstream process with minimum waste generation. This research focused in deducing kinetic mechanism, rate-limiting step and developed kinetic rate law specifically for the biodiesel production catalyzed by green CaO nanocatalyst derived from waste cockle shell via thermal hydrationdehydration treatment. In addition, the CaO nanocatalyst preparation method via thermal hydration-dehydration related parameters (hydration duration, recalcination temperature and recalcination duration) were studied and optimized. The transesterification reaction catalyzed by CaO nanocatalyst followed the Langmuir-Hinshelwood kinetic mechanism with surface reaction as the rate-limiting step. The relatively low activation energy (3786.7 J/mol) for transesterification reaction offered by the CaO nanocatalyst had speed up the reaction rate to 27.3% FAME yield / hr. The optimum condition for the thermal hydration-dehydration treatment used to develop nano CaO catalyst were at 6 h of hydration duration, 650 oC of recalcination temperature and 3 h of recalcination duration. 82 % of biodiesel yield was obtained at moderate temperature of 60 oC and at 5 h reaction time during the transesterification of palm oil catalysed by the nan o CaO. SEM, BET and TPD results proved the CaO nanocatal yst with the existence of large surface area (13.91 high pore volume ( 0.031 8 cm 3 /g) 13 m 2 /g) and that are rich in vacant active sites (1046.46 μmol CO 2 /g) and the pore diameter (33.1 7 nm) were accessible (triglycerides, methanol) and products (FAME, glycerol).